Immune checkpoint inhibitors in cancer therapy: Review of orofacial adverse events and role of the oral healthcare provider - Klein, Brittany A.; Shazib, Muhammad Ali; Villa, Alessandro; de Abreu Alves, Fábio; Vacharotayangul, Piamkamon; Sonis, Stephen; Fedele, Stefano; Treister, Nathaniel S. (Frontiers in Oral Health, 2022)
Immune checkpoint inhibitors (ICIs) are a revolutionary class of antineoplastic therapy that restore anti-tumor immunity. Consequences of this enhanced immune response include a multitude of immune related adverse events (irAEs) that can affect any body system, including the mouth. Orofacial irAEs reproduce features of numerous immune-mediated conditions, including oral lichen planus, mucous membrane pemphigoid, and Sjögren syndrome, among others. The aim of this review is to summarize known orofacial irAEs and to familiarize oral healthcare providers with how to identify and manage these toxicities as part of the care team for patients treated with ICIs.